HTSlib-js: Developer toolkit for a client-side JavaScript interface for HTSlib - Park, Jeongbin; Childs, Liam H; Schlesner, Matthias; Eils, Roland (bioRxiv, 2018)
Background: An increasing number of bioinformatics tools are developed in JavaScript to provide an interactive visual interface to users. However, there are no tools yet that enable fast client-side analysis of large, high-throughput sequencing file formats, such as BAM and VCF files. Results: We present HTSlib-js, an asm.js-based JavaScript wrapper for HTSlib, the de facto standard for processing BAM and VCF files. HTSlib-js exploits recent technological advances in web browser engines that dramatically increase the performance of browser-based tools to enable swift processing of files in the aforementioned formats. HTSlib-js enables quick development of JavaScript-based applications that include processing of aligned sequence reads and variant calling data. Conclusions: HTSlib-js constitutes a toolkit for developers to easily write fast, accessible, browser-based applications that place an emphasis on data visualization, interactivity and privacy. Real-world examples demonstrate the capabilities of HTSlib-js and serve as guide for own developments.